Indonesia's Position As Mediating State In Handling The Conflict Russia-Ukraine Conflict Based On The Concept Of Responsibility To Protect (R2P) - Ajawaila, Della Paula (Fakultas Hukum Universitas Widya Mataram, 2024)
Russia-Ukraine Conflict in the Perspective of International Law” Indonesia's current position is an active mediator so that it must strive non-formally and formally. Indonesia is the president of the G20 which has a strong role because this conflict has an impact on the economy. What Indonesia is doing is referring to the pursuit of peace, m to build international stability. The type of research used by the author is normative research. Normative research is a type of legal research derived from scientific research procedures in order to find the truth based on legal objectives from the normative side. “Responsibility to Protect” is a principle in international relations that aims to prevent genocide, war crimes, ethnic cleansing and crimes against humanity. State action in carrying out humanitarian interventions is often based on the reason that there has been an extraordinary humanitarian tragedy that can threaten international peace and security as the goal of the United Nations.